AGROBACTERIUM-MEDIATED TRANSFORMATION OF CISSAMPELOS PAREIRA LINN: FACTORS AFFECTING ON TRANSIENT GUS EXPRESSION - MUSTRAHALLY RAJAGOPAL; BATHULA SRINIVAS (International Journal of Pharma and Bio Sciences, 2013)
Optimization of co-cultivation parameters during Agrobacterium–mediated transformation to Cissampelos pareira evaluated were bacterial density, infection period, wounding and pre-culture of explants, acetosyringone (AS) concentration and co-cultivation temperature. Optimized parameters resulted in high transformation efficiency at transient GUS expression were as follows; Agrobacterium tumefaciens growth phase of A600nm 0.17, infection period of 30 min, addition of acetosyringone (AS) in co-cultivation medium (50µM) and in bacterial growth culture (800µM) and co-cultivation temperature of 25oC. Higher bacterial density resulted in more transformation efficiency, but also higher necrosis in the explants. Dilution of bacterial suspension reduced necrosis in explants and resulted in higher transformation. The transformation efficiency was increased 6 fold when the infection process was carried out with acetosyringone in co-cultivation medium (50µM) and in bacterial culture (800µM).Our studies proved that among the optimized conditions; the concentration of acetosyringone was the critical parameter during co-cultivation process in Agrobacterium mediated transformation.